Batch and continuous biogas production arising from feed varying in rice straw volumes following pre-treatment with extrusion. (March 2015) - Menardo, S.; Cacciatore, V.; Balsari, P.
Highlights: About 700 million tons of rice straw are produced in the world every year. Anaerobic digestion may offer a good alternative approach to appraise rice straw. Low rice straw content can equilibrate the C:N ratio of the diet for AD plants. Extrusion improved rice straw degradation, with a positive energy balance. High rice straw amount makes extrusion not energetically advantageous. Abstract: This paper studies the synergistic effects on biogas production obtained when different feedstocks are co-digested with varying proportions of rice straw and explores their behavior at the laboratory scale in continuously stirred digesters. Evaluative measures included methane production, volatile solids degradation, ash accumulation, and extrusion effectiveness. The effect of extrusion on the production of energy was also investigated. Results indicated that continuous stirred digesters fed with substrates composed of 10% or 30% of ensiled rice straw (on total FM) produced 146.1 and 140.0 lN CH4 kg DM −1 day −1, respectively. When extrusion was employed, organic matter degradation was promoted and methane production was significantly raised—by as much as 16%. For the feeds containing 10% rice straw, the increase in obtained energy was higher than the energy needed for the extrusion, but the energy balance was close to zero when the percentage of rice straw was the 30% of the feed.